(untitled) (Bangladesh Oncology Journal, 2009)
Ovarian tumour occur at any age group. So pregnancy with ovarian cyst is not very uncommon. But pregnancy with large tumour is uncommon. A 25 years old lady was admitted in BSMMU with 3rd gravida 28 weeks pregnancy with large ovarian tumor with ascites with H/O previous two caesarean section. Ovarian tumour was diagnosed at her 24 weeks pregnancy by ultrasonography. FNAC was done by the advice of her clinician which reveal dysgermenoma. She was referred to BSMMU from cancer Institute, Mohakhali for termination of pregnancy. Key word: Dysgerminoma. (Bang. Onc. J. 2009; 4 (2) : 88-89)